A wild circulation: High presence of Porcine circovirus 3 in different mammalian wild hosts and ticks. Issue 4 (10th April 2019) - Franzo, Giovanni; Grassi, Laura; Tucciarone, Claudia Maria; Drigo, Michele; Martini, Marco; Pasotto, Daniela; Mondin, Alessandra; Menandro, Maria Luisa
Summary: Porcine circovirus 3 (PCV‐3) has emerged as a potential threat for swine industry, being consistently reported in the presence of several clinical signs all around the world. Recently, its presence in wild boar has been demonstrated at high prevalence. This evidence is surprising since the lower density of wild populations might not be expected to sustain such efficient viral transmission. Porcine circoviruses were proven to exhibit a certain plasticity in the host tropism and were detected in unrelated species, like mice, dogs and ruminants. However, if this scenario applies also to wild animals remains to be established. Therefore, this study aimed to investigate the presence of PCV‐3 in wild ungulates other than wild boar and in related hematophagous ectoparasites. One hundred and nine animals were sampled from different hilly and mountain areas of Friuli Venezia Giulia, including 9 chamois ( Rupicapra rupicapra ), 17 red deer ( Cervus elaphus ), 4 mouflons ( Ovis musimon ), 50 roe deer ( Capreolus capreolus ) and 29 wild boars ( Sus scrof a). Additionally, host‐matched ectoparasites were collected when present. Porcine circovirus 3 was diagnosed using molecular techniques and sequencing. This study results confirmed the high PCV‐3 occurrence in wild boar and reported for the first time its presence, at low prevalence, in chamois and roe deer. Moreover, two ticks ( Ixodes ricinus ), one of which non‐engorged, collected from PCV‐3 negative roe deer, tested PCV‐3 positive. The genetic characterization of some of the strains collected from non‐swine hosts allowed to prove that, albeit clearly part of PCV‐3 species, they were genetically unique, demonstrating the absence of among‐samples contamination and thus confirming the actual presence of PCV‐3 genome in these new hosts. Therefore, this study highlights an unexpected broad PCV‐3 distribution and circulation in the wild, rising further questions on porcine circoviruses infectious cycle, epidemiology and origin, which will deserve additional investigations.